“Enfant prodige” della menzogna - Lanati, Barbara (Filosofia, 2017)
The labyrinth of Edgar Allan Poe’s life. His attempts to give shape to a form of autochthonous literature which could go beyond what to him was a provincial, secondary literature, the American one, vis-à-vis the English literature. His attempt to reach a universal audience.